2016
DOI: 10.1016/j.joco.2016.01.004
|View full text |Cite|
|
Sign up to set email alerts
|

Visual management of aphakia with concomitant severe corneal irregularity by mini-scleral design contact lenses

Abstract: PurposeTo evaluate visual results, comfort of use, safety, and efficacy of mini scleral contact lenses in optical management in patients with traumatic aphakia and severe concomitant irido-corneal injury.MethodsIn a case series, eight eyes with post traumatic aphakia and severe concomitant irido-corneal injury that were evaluated at the Contact Lens Clinic of Farabi Eye Hospital, Tehran, Iran for contact lens fitting and could not be corrected with conventional corneal RGP contact lenses were fitted with minis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Aphakia, when unilateral, produces significant aniseikonia, thus limiting the use of spectacles for optical correction. SCLs, specifically the mini-scleral design (MSD), are a good option for managing traumatic aphakia with concomitant irregular astigmatism secondary to corneal scarring [ 54 ]. Alipur and Hosseini evaluated the visual outcomes of the MSD in the optical treatment of individuals with traumatic aphakia associated with iridocorneal injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aphakia, when unilateral, produces significant aniseikonia, thus limiting the use of spectacles for optical correction. SCLs, specifically the mini-scleral design (MSD), are a good option for managing traumatic aphakia with concomitant irregular astigmatism secondary to corneal scarring [ 54 ]. Alipur and Hosseini evaluated the visual outcomes of the MSD in the optical treatment of individuals with traumatic aphakia associated with iridocorneal injury.…”
Section: Discussionmentioning
confidence: 99%
“…The VA significantly improved in all of the assessed eyes, and the average time spent comfortably wearing the MSD was 11.6 h (range 8–16 h). The only adverse effect observed was mild redness in two cases [ 54 ]. High ametropia (non-aphakic), as stated above, was first corrected with SCLs by August Müller in 1889 [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 1967, a large rigid lens, the Apex lens, was designed to provide mechanical stability [630], and is the basis for more recent lens designs. More recently, a mini-scleral lens design has been successfully fitted for severe corneal irregularity and aphakia after trauma [640].…”
Section: Aphakiamentioning
confidence: 99%
“…However, soft lenses can be fitted initially followed by refitting with rigid corneal lenses if adequate vision cannot be achieved with soft lenses [647]. Scleral lenses were a safe and effective option to improve vision with reasonable comfort [640]. In cases of traumatic aphakia with additional complaints of photophobia from traumatic aniridia, rigid corneal lenses made of fluorosilicone acrylate with a dark brown tint have been fitted with success and decreased photophobia [632].…”
Section: Aphakiamentioning
confidence: 99%
“… 39 In addition, two separate studies conducted in recent years reported that mini-scleral and scleral lenses can also be used as safe and effective options in aphakic children. 40 , 41 …”
Section: Introductionmentioning
confidence: 99%